Archaeological results (Scottish Historical and Archaeological Internet Reports, 2010)
A total of eleven archaeological sites were identified by the environmental impact assessment. Sites in Area 1 included a clearance cairn, a lithic scatter below a modern cairn and a burial cairn. Sites in Area 2 included a lithic scatter at Dun na Cluaich, pits, postholes and a lithic scatter at North Aldie Farm.